Cross-sectional Relationships Between Alternate Healthy Eating Index (AHEI) with General and Abdominal Obesity and Blood Pressure in Iranian Hospital Employees - Mirashrafi, Shahrzad; Kafeshani, Marzieh; Hassanzadeh, Akbar; Entezari, Mohammad H. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background and Aims: Due to the increasing prevalence of obesity and related disorders, there is an urgent need to examine the relationship between diet quality and public health. The Alternative Healthy Eating Index (AHEI) is one of the indices that is used to assess diet quality. Therefore, we investigated the relationship between AHEI and anthropometric measurements and blood pressure. Methods: In this cross-sectional study, 127 male and female hospital employees were examined. The AHEI was calculated by a 168 items Food Frequency Questionnaire. Body weight, height, Body Mass Index (BMI), Waist Circumference (WC), Waist-to-Hip Ratio (WHR) and blood pressure were measured by skilled nutritionists. Physical activity level was also obtained by International Physical Activity Questionnaire (IPAQ). Results: The mean total AHEI score in participants was reported as 47.1±6.9 (min=31.9, max=60.3). The mean differences of total AHEI score across the obese/non-obese employees were not statistically significant (P>0.05). Furthermore, there was no significant correlation between total AHEI score and BMI (r=0.019), WC (r=0.022), WHR (r=-0.102), systolic (r=-0.133) and diastolic blood pressure (r=-0.040) (P>0.05). The score of nuts and soybeans was inversely related to the WHR (P=0.008) and systolic blood pressure (P=0.030). Cereal fiber score had a negative relationship with BMI (P=0.02), WC (P=0.03), WHR (P=0.004) and systolic (P<0.001) and diastolic blood pressure (P=0.012). Conclusion: Consumption of nuts and soybeans -one serving per day- can be associated with WHR and systolic blood pressure reduction. More studies with a larger scale are needed to examine diet quality.
Keywords: Alternative healthy eating index